DEVELOPMENT OF E-COMMERCE IN THE ECONOMY OF UZBEKISTAN - Arzuova Shargul Ansatbaevna (Scholar Express Journals, 2022)
The development of innovations and economic relations arising from the implementation of e-commerce operations using new technologies in commercial banks of the republic are considered.
Keywords: Innovation; digital economy; innovation activity; technology